The Effects of Psychodrama on the Health of Adolescent Girls: A Systematic Review - Faezeh Daemi; Seyedeh Fatemeh Vasegh Rahimparvar (Iran University of Medical Sciences, 2018)
Background: During the growth process, young adults are often exposed to and involved in a number of risky behaviors which can have permanent social and health-related consequences. Moreover in clinical practice with adolescents, they frequently miss to comply with a therapeutic program. In this regard, designing proper interventions for adolescent behaviors is necessary. Psychodrama is a kind of non-scripted theater often used as a psychotherapy. The purpose of this review is to determine the effect of psychodrama on the health of adolescent girls.  Methods: Resources were searched in the databases of Scopus, Ovid, Science Direct, PubMed, Web of Science, IranMedex, and SID, with keywords of "psychodrama", "adolescence", "teenager", "health", and "girls." Both English and Persian resources without time limitation were reviewed.  Results: In total, 1840 relevant studies were found. By respecting inclusion criteria, 8 interventional studies were selected to be included in this review. In these studies, some of the effects of psychodrama, such as improving anxiety, depression, oppositional deviant disorder, hyperactivity, frustration, emotional regulation, aggression, conflict resolution skills, forgiveness, self-esteem, and communication skills were determined. Conclusion: The study results indicate improvement of some topics of mental or social health of the adolescent girls. It is suggested that other topics of mental and social health be investigated and more valid studies be designed on the effects of psychodrama on the mental and social and physical health of adolescent girls.